2001
DOI: 10.1007/s100160010008
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Perioperative Stroke after Carotid Endarterectomy: Special Considerations in Symptomatic Patients

Abstract: In order to maximize the efficacy of carotid endarterectomy (CEA), the rate of perioperative stroke must be kept to a minimum. A recent analysis of carotid surgery at our institution found that most perioperative strokes were due to technical errors resulting in thrombosis or embolization. From 1992 through 1997 we have performed nearly 1200 additional CEAs; the purpose of this study was to examine recent trends in the causes of perioperative stroke, with specific attention to differences in symptomatic and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The only identified predictor of perioperative stroke and mortality in this series was intraoperative neurological change after carotid cross‐clamping, necessitating the placement of an intra‐arterial shunt. Whereas this finding confirms previous reports, these studies also purport that other factors such as preoperative stroke or contralateral carotid artery occlusion significantly increase the stroke risk 17,22,26,27 . Our large series does not support these claims, showing clamp intolerance and subsequent shunting to be a strong and the sole predictor.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The only identified predictor of perioperative stroke and mortality in this series was intraoperative neurological change after carotid cross‐clamping, necessitating the placement of an intra‐arterial shunt. Whereas this finding confirms previous reports, these studies also purport that other factors such as preoperative stroke or contralateral carotid artery occlusion significantly increase the stroke risk 17,22,26,27 . Our large series does not support these claims, showing clamp intolerance and subsequent shunting to be a strong and the sole predictor.…”
Section: Discussionsupporting
confidence: 75%
“…Analysis showed that patient characteristics and comorbidities were not predictors. Traditionally, contralateral carotid artery occlusion has been considered a significant predictor of perioperative stroke and poor outcome 12,22 . Although our series showed that this was an important predictor of intraoperative neurological change necessitating shunting, the status of the contralateral carotid artery was unimportant in predicting perioperative stroke and death.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Periprocedural strokes during carotid endarterectomy might have multiple causes but have been shown to frequently originate from plaque thrombosis and embolization. 48 Although the mechanisms underlying the observed associations remain unknown, they might relate to the higher risk of periprocedural microembolization previously reported to be more common in patients with features of vulnerable plaques. 27,49 To our knowledge, there has been only one small phase II trial targeting MCP-1 signaling in the context of human atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…Intraoperative thromboemboli occur during cross-clamping, arteriotomy, shunt placement and vessel closure by disrupting the atheromatous plaque, and stimulating local platelet activation and aggregation 28 30 31. In CAS, thromboemboli may arise as a result of plaque disruption at the site of intervention, protrusion of the thrombus through open cell stents with subsequent embolisation, or more proximally from the aortic arch during device introduction 32.…”
Section: Mechanisms Of Perioperative Strokesmentioning
confidence: 99%